Rainforests : Land use options for amazonia - Johnson, Craig; Oxford University press. WWF; Knowles, Richard; Colchester, Marcus; WWF. (Great Britain : Oxfords University Press.WWF, 1989)
Consisting of teacher's notes and photocopyable student activity sheets, this resource pack accompanies an A-level text which provides detailed material on the plight of the Amazon rainforest
Keywords: Rain forest ecology -- Amazon River Valley; Land use -- Amazon River Valley; Rain forests